Jesus camp (Magnolia Home Entertainment, 2006)
"Follows Levi, Rachael, and Tory to Pastor Becky Fischer's 'Kids on Fire' summer camp in Devil's Lake, North Dakota, where kids as young as 6 years-old are taught to become dedicated soldiers in 'God's army'. The film follows these children as they hone their 'prophetic gifts' and are schooled in how to 'take back America for Christ'"--Container